From Paper to Pixels: The Influence of Digital Accounting Tools on Financial Practices and Performance of Indonesian MSMEs - Mohamad Apri Atmaja; Zidan Restu Saputra; Acep Komara; Arinal Muna (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study assesses whether perceived ease of use, perceived usefulness, perceived trust, and perceived security can influence an individual's increased intention to use financial reporting services using a digital accounting application. This study employs a qualitative approach, utilizing a direct sampling method through an interview process that lasts approximately 10 minutes and is recorded live in audio format. The following procedure is the audio that was transcribed and included in the article. The target population of this study was 20 MSMEs engaged in services, sales, culinary, and food and beverage (F&B). The sampling technique used was snowball sampling. With this sampling, researchers were able to search for data with a small number of respondents who had met the research criteria, with the resulting sample containing as many as 20 respondents. The results of the study indicate that perceived ease of use, perceived usefulness, perceived trust, and perceived security can significantly influence an individual's intention to use financial reporting services using a digital accounting application. Specifically, perceived ease of use and perceived usefulness have a positive impact, indicating that better financial understanding is met with a higher tendency to adopt digital financial services. However, these findings also highlight the need to increase knowledge in preparing good and correct financial reports, especially among micro and small-scale entrepreneurs.